2005
DOI: 10.1158/0008-5472.can-04-3337
|View full text |Cite
|
Sign up to set email alerts
|

Activated Marrow-Infiltrating Lymphocytes Effectively Target Plasma Cells and Their Clonogenic Precursors

Abstract: A major limitation of adoptive immunotherapy is the availability of T cells specific for both terminally differentiated tumor cells and their clonogenic precursors. We show here that marrow-infiltrating lymphocytes (MILs) recognize myeloma cells after activation with anti-CD3/CD28 beads with higher frequency than activated peripheral blood lymphocytes from the same patients. Furthermore, activated MILs target both the terminally differentiated CD138 + plasma cells and the myeloma precursor as shown by profound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 48 publications
5
84
0
Order By: Relevance
“…[37][38][39][40] The promotion of a tolerant microenvironment by tumors through mechanisms of antigen-presentation impairment, defects in TCR signaling, and introduction of immunosuppressive factors has been well characterized. [41][42][43][44][45][46][47] Within antigen-specific CD4 C T cells specifically, both in vivo and in vitro studies have demonstrated that they become tolerant during tumor growth. 42 T cells are not primed and rendered unresponsive during tumor progression, a mechanism found in both solid and hematologic tumors.…”
Section: E1051922-6 Volume 4 Issue 12 Oncoimmunologymentioning
confidence: 99%
“…[37][38][39][40] The promotion of a tolerant microenvironment by tumors through mechanisms of antigen-presentation impairment, defects in TCR signaling, and introduction of immunosuppressive factors has been well characterized. [41][42][43][44][45][46][47] Within antigen-specific CD4 C T cells specifically, both in vivo and in vitro studies have demonstrated that they become tolerant during tumor growth. 42 T cells are not primed and rendered unresponsive during tumor progression, a mechanism found in both solid and hematologic tumors.…”
Section: E1051922-6 Volume 4 Issue 12 Oncoimmunologymentioning
confidence: 99%
“…In addition to these vaccine-based approaches, a number of other cellular therapy strategies (Table 4) Marrow-infiltrating lymphocytes Borrello and colleagues at Johns Hopkins demonstrated that MILs were phenotypically and functionally different from PBL, with greater proportion of central memory T cells, greater recognition and killing of myeloma cells upon re-activation, and greater capacity for trafficking to the marrow/tumor microenvironment. 13 This led to a phase I trial of adoptive transfer of autologous, ex vivo-activated MILs on day +3 following high-dose melphalan and auto-HCT in myeloma patients. Initial results from 22 patients demonstrated that the generation and infusion of large numbers of activated MILs was feasible and safe, with mild autologous GVHD of the skin (not requiring therapy) seen in 32%.…”
Section: Cellular Therapiesmentioning
confidence: 99%
“…However, these myeloma-associated immune responses (IRs) could be restored ex vivo with appropriate stimulation. 12,13 Humoral and cellular IRs against myelomaassociated Ags such as Wilm's tumor 1 (WT1) and the type I melanoma Ag gene (MAGE) proteins MAGE-A3 and CT7 (MAGE-C1) were detected in untreated PCM patients and after auto-or allo-HCT. In the allo-HCT setting, these IRs were associated with improved outcomes, and myeloma Ag-specific T cells from patients could kill both human myeloma cell lines and autologous PCM cells.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Furthermore, bone marrow-residing memory T cells are involved in the control of dormant hematologic malignancies, 20 and, in patients with myeloma, such bone marrow-infiltrating lymphocytes have the potential to target myeloma cells and their precursors. 21 Based on these findings and the fact that the bone marrow represents the immediate tumor environment of myeloma, we conducted the first study focusing on marrow-residing CD4 …”
mentioning
confidence: 99%